2016
DOI: 10.1097/md.0000000000002820
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Diastolic Dysfunction Assessed by Conventional Echocardiography and Spectral Tissue Doppler Imaging in Adolescents With Arterial Hypertension

Abstract: Compared to conventional echocardiography, spectral tissue Doppler imaging (s-TDI) allows more precise evaluation of diastolic cardiac function. The purpose of this study was to conduct s-TDI to analyze the slow movement of the left ventricular (LV) myocardium in adolescents with systemic arterial hypertension (HT) and to determine whether patients with HT suffer from LV diastolic dysfunction. The study group comprised 69 consecutive patients (48 boys and 21 girls aged 14–17 years [mean, 15.5 ± 1.1 years]) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…E/A ratio usually decreased to be less than 1 in patients with diastolic dysfunction. [ 33 , 34 ] A higher E/A ratio in group 1 likely represents a less degree of diastolic stiffness, and therefore a better cardiac preload reserve, [ 35 ] which in itself would predict a better response to 6MWT. The present study showed that group 1 had significantly higher 6MWD than group 2 (515.38 ± 24.97 vs 306.39 ± 20.20 m; P = 0.043).…”
Section: Discussionmentioning
confidence: 99%
“…E/A ratio usually decreased to be less than 1 in patients with diastolic dysfunction. [ 33 , 34 ] A higher E/A ratio in group 1 likely represents a less degree of diastolic stiffness, and therefore a better cardiac preload reserve, [ 35 ] which in itself would predict a better response to 6MWT. The present study showed that group 1 had significantly higher 6MWD than group 2 (515.38 ± 24.97 vs 306.39 ± 20.20 m; P = 0.043).…”
Section: Discussionmentioning
confidence: 99%
“…There were 2860 individuals aged 5-19 years in 17 studies [16][17][18][19][20][21][22][23]26,27,[29][30][31][32][33][34][35] who underwent evaluation of any measure of LV systolic function (Table 1). These included 41% (1168/2860) with elevated BP (including HT), 67% male [sex reported in 16 studies, [16][17][18][19][20][21][22][23]26,27,[30][31][32][33][34][35]). EF was employed to measure LV function in all the 15 studies; FS was analyzed in 11 studies [17,19,20,22,25,26,[29][30][31][32]34]; in five studies [18,20,22,24,…”
Section: Left Ventricular Systolic Functionmentioning
confidence: 99%
“…These changes in diastolic function were subclinical. Childhood studies found higher E/e’ and lower e’/a’ in children with hypertension [40], and hypertrophic cardiomyopathy [41]. However, there is no cutoff value for E/e’ or lateral e’ velocity to indicate diastolic dysfunction in children and adolescents.…”
Section: Limitationsmentioning
confidence: 99%